The BecA ILRI Hub Data Management workshop, 5–16 June 2017 - International Livestock Research Institute (International Livestock Research Institute, 2017)
The Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI) Hub held a Data management and genotyping by sequencing (GBS) workshop from 5–16 June 2017 Nairobi, Kenya. The workshop was attended by twenty participants from national agricultural research systems (NARS) in nine African countries—Burundi, Ethiopia, Kenya, Madagascar, Nigeria, Rwanda, South Sudan and Uganda—and facilitated by trainers from Earlham Institute, UK; Fathom Labs, Kenya; and Ohio State University, USA as well as bioinformatics research associates from the BecA-ILRI Hub. In this 5-minute video, participants share their perspectives on the training and its applications to their research. This video features the song "African Era" by Maryos, available under a Creative Commons Attribution-Noncommercial license.